3 from hell [videorecording (DVD)] - Zombie, Rob, 1965-; Zombie, Sheri Moon, 1970-; Moseley, Bill, 1951-; Brake, Richard, 1964-; Stone, Dee Wallace, 1948- (Lionsgate, 2019)
After barely surviving a furious shootout with the police, Baby Firefly, Otis Driftwood, and Captain Spaulding are behind bars. But pure evil cannot be contained, and a firestorm of murder, madness, and mayhem will be released in this terror ride to Hell . . . and back.